1996
DOI: 10.1046/j.1365-2141.1996.d01-1506.x
|View full text |Cite
|
Sign up to set email alerts
|

G‐CSF alone mobilizes sufficient peripheral blood CD34+ cells for positive selection in newly diagnosed patients with myeloma and lymphoma

Abstract: We have evaluated CD34+ cell positive selection from granulocyte-colony stimulating factor (G-CSF)-mobilized peripheral blood progenitor cells (PBPC) in 26 patients with either multiple myeloma (MM, n = 18) or follicular non-Hodgkin's lymphoma (NHL, n = 8). 26 PBPC were collected with two leukaphereses: 16 contained sufficient numbers of CD34+ cells and were elected. The absolute number of CD34+ cells in the leukapheresis products was found to be significantly related to the duration of underlying disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 9 publications
2
35
1
Order By: Relevance
“…3 Initial trials of autografts with CD34 ϩ PBSCs have mainly been performed in adult neuroblastoma weighing 20 kg or less. Products of two consecutive leukaphereses carried out on a COBE Specpatients [4][5][6] and, outside of our team, 7 and so thus far there have been no reports of studies performed in small children. tra separator after G-CSF alone mobilization were pooled for immunoselection on Ceprate column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Initial trials of autografts with CD34 ϩ PBSCs have mainly been performed in adult neuroblastoma weighing 20 kg or less. Products of two consecutive leukaphereses carried out on a COBE Specpatients [4][5][6] and, outside of our team, 7 and so thus far there have been no reports of studies performed in small children. tra separator after G-CSF alone mobilization were pooled for immunoselection on Ceprate column.…”
Section: Discussionmentioning
confidence: 99%
“…number of progenitor cells as about 50% of CD34 ϩ cells collected are presumed lost during the selection pro-CD34 ϩ cell immunoselection from G-CSF-alone primed PBSCs results in sufficient numbers of progenitor cells per cedure; [4][5][6][7]15,22 (2) the confirmation of the efficacy of selection technique (recovery rate, purity) in the light of differpatient kg to allow transplantation. The overall recovery of CD34 ϩ cells (45.3%) was in accordance with previously ent characteristics of the installed samples (overall cell concentration) when compared to adults; and (3) the sucreported data in adults.…”
mentioning
confidence: 99%
“…[22][23][24] I (18 patients) the progenitor cells were mobilized with highThis strategy has also been applied successfully as a PBPCdose cyclophosphamide (HD-CY), 4 g/m 2 i.v. divided in 2-priming regimen in patients with other poor-risk maligday infusions through a central venous catheter.…”
mentioning
confidence: 99%
“…[25][26][27] Although some authors have pointed out the ration (4 l continuous infusion over 24 h) was initiated 12 h lower stem cell content provided by this approach when before chemotherapy. MESNA (Uromitexan; Asta Medica, compared with chemotherapy followed by cytokines, 28 other Madrid, Spain) was administered half an hour before the start investigators have found no significant differences [22][23][24][25][26] and of CY and continued for the following 24 h. In this group have suggested that PBPC mobilization with the use of a all patients were hospitalized during the administration of growth factor alone could be beneficial, avoiding unnecess-HD-CY and during the subsequent aplasia. ary hospitalization and toxicity during the secondary aplarhGM-CSF (Molgramostim, Sandoz SA/Scheringsia induced by HD-CY.…”
mentioning
confidence: 99%
See 1 more Smart Citation